PENGARUH INFLASI, KURS, DAN SUKU BUNGA TERHADAP PERTUMBUHAN EKONOMI - M. Yazid AR (JURNAL EKOMBIS, 2019)
This study aims to analyze the influence, exchange rates and interest rates on economic growth. Inflation, exchange rates and interest rates are important variables in macroeconomics. This study uses time series data from 1980-2017. To see the effect of the independent variables on the dependent variable, the Ordinary Least Square analysis model is used. The research results obtained: conversion, exchange rates and interest rates are negative and significant to economic growth. Increased inflation, the exchange rate and interest rates will contribute to a decline in economic growth. For this we need monetary policy that is able to provide stimulus to growth, a priority for increasing interest rates. Bank Indonesia as a monoteric authority holder can do it through monetary policy. Inflation and the exchange rate are the consequences of economic openness. Keywords: Inflation, Exchange Rates, Interest Rates and Economic Substitution